Only the paranoid survive how to exploit the crisis points that challenge every company and career - Grove, Andrew (London HarperCollins, 1997)
Few CEOs can claim this level of consistent record-breaking success. Grove attributes much of this success to the philosophy and strategy he reveals in Only the Paranoid Survive--a book that is unique in leadership annals for offering a bold new business measure, and for taking the reader deep inside the workings of a major corporation. Grove's contribution to business thinking concerns a new way of measuring the nightmare moment every leader dreads--the moment when massive change occurs and all bets are off. The success you had the day before is gone, destroyed by unforeseen changes that hit like a stage-six rapid. Grove calls such moments Strategic Inflection Points, and he has lived through several. When SlPs hit, all rules of business shift fast, furiously, and forever. SlPs can be set off by almost anything--megacompetition, an arcane change in regulations, or a seemingly modest change in technology.
Includes index.
Keywords: Intel Corporation; Organizational change; Strategic planning; Technological innovations -- Economic aspects